HEPATIC METASTASIS OF THYMOMA: CASE REPORT OF A FAST-GROWING ABDOMINAL MASS IN A PREGNANT PATIENT - Raspopović, Miloš; Micić, Dušan; Perišić, Zlatko; Arsenijević, Vladimir; Brkić, Dušan N; Gregorić, Pavle (Sanamed, 2023)
Introduction: Thymomas are the most common primary mediastinal tumors originating from epithelial cells of the thymus, demonstrating epithelial differentiation. Pathologically, thymomas exhibit relatively slow growth and typically spread directly, with extremely rare occurrences of distant dissemination to extrathoracic organs. The precise incidence of such dissemination remains unknown. Distant metastases, particularly to the liver, are exceptionally rare, with only a few cases documented in the literature.Case Report: A 39-year-old woman, in her 31st week of gestation, presented with abdominal pain and discomfort. She underwent ultrasonography, followed by an urgent MRI of the abdomen due to a protruding tumor mass in the liver. Shortly after delivering a healthy baby via cesarean section, she was admitted to the hospital for a CT scan of the abdomen. The imaging revealed multiple focal changes in the liver parenchyma, exhibiting radiological characteristics consistent with focal nodular hyperplasia. Less likely differential diagnoses included adenomas or hemangiomas. Subsequently, she underwent staged hepatectomy, and the results of the pathological analysis confirmed the presence of type B thymoma metastases in the liver.Conclusion: According to the available data in the literature, metastatic thymomas are often identified in patients who have previously undergone treatment for the primary disease. Our patient did not have a history of thymectomy, as confirmed by postoperative chest scans. Onset of symptoms during late pregnancy guided our diagnosis, relying on overall clinical and radiological findings of the detected tumor. Our treatment involved staged hepatectomy post-childbirth, followed by adjuvant chemotherapy. Further comprehensive studies are essential to precisely understand neoplasm behaviors like thymoma for timely detection and effective treatment.
Keywords: thymoma; metastasis; liver; pregnancy; surgery